Semi artificial breeding of white leg shrimp Litopenaeus vannamei - Ghazi, Abdul-Hussein H.; Al–Noor, Sajed S.; Ali, Malik H. (Iraqi Journal of Aquaculture, 2021)
In this study the breeding of the shrimp Litopenaeus vannamei was achieved by two methods; the first was stock breeding to estimate total number of eggs, and the second was individual breeding to recognize the relationship between weight and eggs number. The environmental factors in the hatchery were measured, the averages of water temperature and salinity were recorded to be 31 º C and 32 ppt., respectively, while the dissolved oxygen and pH were 7.5 mg/ l and 8.2 respectively. The results of stock breeding showed that total number of eggs (fecundity) and nauplii produced from 20 ablated females with weight of 35.5 + 3.1 g were 3000000 eggs per spawning and about 2 400000 nauplii respectively. Fertilization rate and hatching rates were 86.5 %, and 78.7 % respectively. The results of individual breeding showed that maximum number of eggs (164000 eggs / female) was achieved in these females that weight 42.0 g, while the minimum were 95000 eggs / female for female weighted 32.5 g. Maximum fertilization rate was 95.2 % in those females with lower weight, while the minimum fertility rate was 77.5 % in those with higher weight.